Significance of reaction CH3 + NO = H2CN + OH in two-stage ignition of nitromethane. (15th November 2019) - Shang, Yanlei; Shi, Jinchun; Ning, Hongbo; Zhang, Runtong; Luo, Sheng-Nian
Graphical abstract: Highlights: Two-stage ignition delay times are measured at broader experimental conditions. First-stage ignition delay time decreases with increasing equivalence ratio below 1150 K. The intensity of second OH* peak is indiscernible at fuel-rich or low temperature condition. CH3  + NO = H2 CN + OH shows importance for second-stage ignition at fuel-rich condition. Abstract: Two-stage ignition of nitromethane diluted in Ar is investigated at various equivalence ratios (0.2–0.5), dilution levels (93%–97%), and pressures (4–16 atm) with a heated shock tube apparatus. OH* emission profiles are used to determine ignition delay times. The second-stage ignition delay time increases with increasing equivalence ratio or dilution level, but is insensitive to pressure especially at high dilution levels. The first-stage ignition delay time is unaffected by the present experimental parameters above 1150 K, below which it decreases with increasing equivalence ratio or pressure. An updated model reconsidering reaction CH3  + NO = H2 CN + OH is examined against the experimental measurements from present work and literature, including ignition delay times, laminar burning velocities, and species mole fraction profiles. At fuel-rich condition, this reaction has a significant contribution to the formation of OH radical during the second-stage ignition. The two-stage ignition and intensity evolution of OH peaks are well predicted and explained kinetically by the updated model.